Quality of Life and low back pain in primary caregivers of children with cerebral palsy - Eduardo Borba Neves; Evelise Fernandes Pietrovski; Rafaela Franco Claudino (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2015)
The aim of this study was to evaluate the quality of life of primary caregivers of children with CP, correlating with the presence of low back pain and motor impairment level of the child. For this research to have been carried out there was the participation of 55 primary caregivers that completed the questionnaires of Roland & Morris (QRM) and WHOQOL-Bref. The evaluation of children's motor impairment was measured by Gross Motor function Classification System (GMFCS). The results show that primary caregivers of children with CP had a loss in their quality of life, especially in the environmental domain and facet pain and discomfort (30.45), negative feelings (34.09), and recreation and leisure (37.27). There were no significant correlations between motor impairment in children with CP, the quality of life of their primary caregivers, and the symptoms of low back pain. However, it was observed that the average symptoms of low back pain are lower in caregivers of children with minor motor impairment (p=0.488), and that there is a significant negative correlation (r=-0.508, p<0.001) between the symptoms of back pain and quality of life of caregivers.